2023
DOI: 10.1177/17151635231176270
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing mifepristone for medical abortion in Canada: Pharmacists’ experiences of the first year

Abstract: Background: Mifepristone for medical abortion was first dispensed by community pharmacists in Canada directly to patients in January 2017. We asked about pharmacists’ experiences over their first year dispensing mifepristone in order to evaluate the frequency of the new practice and assess availability in urban/rural pharmacies. Methods: From August to December 2019, we invited 433 community pharmacists who had completed a baseline survey at least 1 year prior to participate in a follow-up online survey. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…13,14 In these pilot programs, patients who received pharmacist-provided abortion medication and follow-up care reported having satisfactory abortion experiences. 13,14 Additionally, previous studies conducted in the US and Canada, [14][15][16][17][18][19][20] where dispensing of medication abortion by pharmacists has been legal since 2017, demonstrate pharmacists' willingness to dispense medication abortion. Among US-based pharmacists, benefits to dispensing medication abortion include the ability to expand abortion access to patients, improve patients' quality of care, streamline delivery of health care services, and make use of pharmacists' expertise.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…13,14 In these pilot programs, patients who received pharmacist-provided abortion medication and follow-up care reported having satisfactory abortion experiences. 13,14 Additionally, previous studies conducted in the US and Canada, [14][15][16][17][18][19][20] where dispensing of medication abortion by pharmacists has been legal since 2017, demonstrate pharmacists' willingness to dispense medication abortion. Among US-based pharmacists, benefits to dispensing medication abortion include the ability to expand abortion access to patients, improve patients' quality of care, streamline delivery of health care services, and make use of pharmacists' expertise.…”
Section: Introductionmentioning
confidence: 93%
“…14,16,20 Studies conducted in Canada found similar barriers to dispensing medication abortion among pharmacists, with the addition of having low demand among patients, drug shortages, and short expiration dates. [17][18][19] Indeed, more information is needed to inform public health efforts to expand the provision of medication abortion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations